PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA SNVT PELAKSANAAN JARINGAN PEMANFAATAN AIR POMPENGAN JENEBERANG SUL-SEL - Susianti andi; jam'ah jam'ah; alamsyah alamsyah (Jurnal Ilmu Manajemen Profitability, 2017)
The purpose of this study is to empirically test the effect of compensations and work enviroment on employee work productivity and to find out which variable has the most influence on employee work pproductivy perception the study was conducted by survey method, where data was obtained by questionnaire distribution on 56 respondents. The population in this study were all SNVT employees implementing the network of pompengan water utilization in south sulawesi. The sampling method is stratified random sampling, the data obtained is then analyzed using muiltple linear regression analysis consisting of the f test and and t test and the results of the t test, t count t table (2,4211,674) and the test statistic f from the table obtained f count value of 6,850 with a probability value (sig) =0,002, f count value (6,850) f table (3,18). Based on the results of this study, it can be conculuded that compesation and work environment have a positive and significant effect on employee work productivity on SNVT implemantation of the pompengan water utilization network  in south sulawesi